Perspectives on the evaluation of rules for the social implementation of autonomous robots (on viewpoints for evaluating various rules). (3rd May 2021) - Arai, Koki
ABSTRACT: Various guidelines for the social implementation of autonomous robots have been developed so far; however, how these guidelines are used remains an issue. In this study, the concept of legitimacy is used as a criterion to evaluate such guidelines. From the perspective of legitimacy, sociological acceptance, moral legitimacy, and future expectations can be considered constitutional and legal perspectives when addressing the necessary conditions for the social implementation of autonomous robots. At the same time, the article considers that resources, reflections, expertise, recognitions, and results are required as sufficient conditions of the elaboration likelihood model. As a case study, an examination of the Japanese government's approach to ethics extracted the need for moral legitimacy and the need for resources and advice from a professional perspective on ethics to obtain adequate outcomes. It has contributed to this paper by presenting a review process, in which the necessary and sufficient conditions for consideration must be examined from the perspective of legitimacy.